Diaphragm dysfunction from phrenic nerve injuries during LVAD or heart transplant: Positive role of diaphragm pacing - Christina S. Boutros, DO; MaryJo Elmo, ACNP; Nicholas Carl, BS; Yasir Abu-Omar, MD; Rakesh Arora, MD; Yakov Elgudin, MD, PhD; Kelsey E. Gray, MD; Marc P. Pelletier, MD; Raymond P. Onders, MD, FACS (JHLT Open)
Background: Phrenic nerve dysfunction in left ventricular assist device (LVAD) implantation or heart transplant (HTx) leads to dependency on noninvasive ventilation and difficulty weaning off mechanical ventilation (MV). This study reports on diaphragm pacing (DP) to improve diaphragm function postphrenic nerve injury. Methods: In a single-center cohort study, 2 DP systems were used in HTx or LVAD recipients. Chronic DP was laparoscopically implanted for remote phrenic dysfunction, while temporary DP was implanted percutaneously during HTx. Diaphragm function was evaluated radiographically and via electromyography. Results: Out of 900 patients, 10 met criteria and used DP without adverse events. Eight had chronic DP for phrenic injuries (5 HTx, 3 LVAD), with 87% recovery. Two had temporary DP at HTx; one utilized DP for weaning from MV. Early DP use facilitated rapid MV weaning. Conclusions: This exploratory case series suggests a potential role for DP in patients with phrenic nerve injury following heart transplant or LVAD.